The Role of Sosial, and Emotional Learning (SEL) in Improving Student Wellbeing and Academic Success - Nisa, Khoirun; Abdullah, Abdullah (Universitas Nurul Jadid, 2023)
This research focuses on the role of Social-Emotional Learning (SEL) in improving students' mental well-being and academic performance. The main objective of this study is to understand how the implementation of Social-Emotional Learning programs can affect students' emotional states and educational outcomes. Evaluate the extent to which the Social-Emotional Learning program can help students manage stress, anxiety, and depression, and improve academic performance. The research method used is a qualitative approach with data collection techniques through observation and in-depth interviews with the head of madrasah, teachers, curriculum deputy head, student guardians, and students. Data analysis was done thematically to identify the main themes related to the effects of the Social-Emotional Learning program. The results showed that the Social-Emotional Learning program significantly improved students' mental well-being, which had a positive impact on motivation, learning focus, and academic achievement. In addition, students involved in Social-Emotional Learning programs can better recognize and manage emotions, which can reduce stress and anxiety levels. The implications of this study emphasize the importance of integrating Social-Emotional Learning programs into the education curriculum to create a more inclusive learning environment that supports student development and achieves holistic and comprehensive education outcomes.